THE STUDENT’S PERSPECTIVE OF THE EMPLOYEE AND THE REGULAR CLASS OF CHEMICAL TECHNOLOGY STUDY PROGRAM IN LEARNING ENGLISH FOCUSING ON THE SUGARCANE PROCESSING AT POLYTECHNIC LPP YOGYAKARTA: A NEED ANALYSIS - Endang Lestari (Sean Institute, 2023)
Nowadays, The Indonesian Ministry of Education launched nine wedding packages for vocational education in the industrial world. The courses must have an industrial link. English courses for vocational education must be in line with students’ needs. Therefore, it is necessary to have a common perception of the English learning needs of regular students and employee students in a similar study program. This study is a descriptive quantitative that aims to find out and compare the perceptions of regular students with employees majoring in chemical technology that focuses on sugar processing in learning English at Polytechnic LPP Yogyakarta. There were 25 respondents comprising seventeen from the regular class and eight from the employee class. The researcher used online questionnaires to collect the data. The quantitative data were analyzed using descriptive statistics. The data with the highest percentage are presented in the table. Based on the need analysis, the student found descriptive, narrative, report, and procedure text in their life. The topics consist of measurement tools, instrumentation, sugar fabrication, and analysis process. Grammar and vocabulary become obstacles in learning English. In speaking activities, they want to have a pair for a conversation. The main goal of learning English is to improve their speaking skills. The role of the lecturer should be interactive with students and apply new technology and fun learning methods. They prefer to work in groups. Online media is their favorite learning source. In general, there are some similarities between regular and employee students' perceptions. The results of this study can be used for developing English material.